OWNERSHIP STRUCTURE AND ORGANIZATIONAL PERFORFORMANCE IN SELECTED LISTED MANUFACTURING COMPANIES, NIGERIA - Aribaba FO; Ahmodu O.A; Olaleye B.R; Yusuff S.A (Management Department, Faculty of Economics and Business, Universitas Jambi, 2019)
This study examines the effect of ownership structure on organizational performance in selected listed manufacturing companies in Nigeria. The study incorporated survey research design. Big five (5) listed manufacturing companies were arbitrarily drawn from the population using judgmental sampling procedure. The sources of data employed were primary and secondary data. The primary data was through questionnaire while the secondary data was obtained through the company’s annual financial report between the periods of 2013 – 2017. The instrument used was validated; Cronbach Alpha method of reliability was employed to test the internal consistency of the instruments. The data collected were analyzed using the statistical package for social sciences (SPSS). The coefficient value of 0.815 revealed that the instruments were reliable against the targeted threshold of 0.7. The statistical method used for this study was a regression (r2) and analysis of variance (ANOVA) to test the individual coefficient and the mean value of the variables correlated. The findings revealed that the estimated model has a weak estimating control. Since about 99.3% of outcomes of performance were unaccounted by the model. Hence, this captured the error term in the model with the Durbin-Watson value of 1.418 which was an indication of the absence of autocorrelation in this model. Based on these findings, the study, therefore, recommends that the stakeholders should expediently adhere to corporate governance principles as its implementation lead to an increase in organization performance.